APPLICATION OF THE WEIGHTED PRODUCT METHOD OF TEACHER PERFORMANCE ASSESSMENT IN PROVIDING LESSONS - Nurdilla Khoirunnisa; Bachtiar Efendi; Andy Sapta (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: A system designed to assist decision-makers in semi-structured situations. Teacher performance appraisal is a technique that will result in better learning using a decision support system. Evaluating teacher performance in providing lessons at SMK Negeri 1 Setia Janji is still carried out conventionally and not in detail. With an assessment that is not detailed, it is feared that there will be a subjective assessment that will result in social jealousy for teachers who have not received learning recommendations. Evaluation at SMK Negeri 1 Setia Janji is still done manually and has not been detailed for teachers who have not received recommendations. So to overcome these problems, a decision support system was designed using the Weighted Product (WP) method. This study uses 6 criteria. The final result of this research is that the decision support system with the Weighted Product (WP) method can handle problems in teacher performance assessment. Keywords: Decision Support System; Teacher Performance Assessment; Weighted Product Abstrak: Sistem yang dirancang agar membantu  pembuat keputusan  pada situasi semi-terstruktur. Penilaian kinerja guru ialah teknik yang akan  menghasilkan pembelajaran yang  lebih  baik menggunakan sistem pendukung keputusan. Proses evaluasi kinerja guru dalam memberikan pelajaran di SMK Negeri 1 Setia Janji masih dilaksanakan secara konvensional dan  tidak terperinci. Dengan penilaian yang tidak terperinci dikhawatirkan akan adanya penilaian yang bersifat subjektif  yang akan mengakibatkan kecemburuan sosial bagi guru yang belum menerima rekomendasi pembelajaran. Evaluasi di SMK Negeri 1 Setia Janji masih dilakukan secara manual dan belum detail untuk guru yang belum mendapatkan rekomendasi. Maka untuk mengatasi permasalahan tersebut, dirancanglah suatu sistem pendukung keputusan menggunakan Metode Weighted Product (WP).  Adapun dalam penelitian ini memakai 6 kriteria. Hasil akhir dari penelitian ini didapatkan bahwa sistem pendukung keputusan dengan metode Weighted Product (WP) dapat menangani permasalahan pada penilaian kinerja guru. Kata Kunci: Penilaian Kinerja Guru; Sistem Pendukung Keputusan; Weighted Product (WP)